Mental Health Conditions and Quality of Life among Online Gambling College Students: A Descriptive Study - Wulandari, Devi; Saputra, Dinar; Ardiansyah, Zaidan (Journal of Educational, Health and Community Psychology, 2024)
The phenomenon of online gambling is widespread among college students in Indonesia. However, little is known about its impact on their mental health and health-related quality of life. This study aimed to examine the mental health and quality of life of college students affected by online gambling. A cross-sectional survey was conducted with online questionnaires distributed to 118 students who had engaged in online gambling within the past 12 months. The Self-Report Questionnaire-20 (SRQ-20) and the 12-Item Short FormHealth Survey (SF-12) were used for assessment. Results showed that Mental ComponentSummary (MCS-12) scores were lower than Physical Component Summary (PCS-12)scores. Respondents reported issues such as sleep disturbances, difficulty enjoying daily activities, fatigue, decision-making struggles, lack of a sense of purpose, feelings of unhappiness and worthlessness, nervousness, and frequent worry. These findings suggest that online gambling may have a harmful effect on students' mental health and overall quality of life.